2005
DOI: 10.1002/pts.697
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen- and light-barrier properties of thermoformed packaging materials used for modified atmosphere packaging. evaluation of performance under realistic storage conditions

Abstract: The oxygen transmission rate (OTR) of packaging materials used for modified atmosphere packaging (MAP) of chilled products varies extensively with temperature, relative humidity (RH) and material thickness after the thermoforming of packages. Two different polymer combinations were studied: APET/PE (tray) and PA/PE (lid). A temperature reduction of 8°C (in the interval 7-23°C) caused an OTR reduction of 26-48% depending on material type, degree of thermoforming and RH. A 2-3-fold increase in OTR was observed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Generally, the oxygen transmission rate (OTR) of films decreases with temperature (Eustace, 1981). For PET/PE films, Jakobsen, Jespersen, Juncher, Miquel Becker, and Risbo (2005) observed that there was a reduction of 37% in OTR when storage temperatures ranged from 23 C to 7 C, and the OTR was not affected by a change in RH. In this case, the low oxygen concentration was maintained, possibly inhibiting growth and activity of aerobic microorganism.…”
Section: Cheese Respiratory Activitymentioning
confidence: 92%
See 1 more Smart Citation
“…Generally, the oxygen transmission rate (OTR) of films decreases with temperature (Eustace, 1981). For PET/PE films, Jakobsen, Jespersen, Juncher, Miquel Becker, and Risbo (2005) observed that there was a reduction of 37% in OTR when storage temperatures ranged from 23 C to 7 C, and the OTR was not affected by a change in RH. In this case, the low oxygen concentration was maintained, possibly inhibiting growth and activity of aerobic microorganism.…”
Section: Cheese Respiratory Activitymentioning
confidence: 92%
“…These working conditions can lead to changes in the gas transfer levels, depending on the material used, the temperature and the RH (De Leiris, 1989). Indeed, the decrease of the OTR due to the decrease of 8 C was estimated at 50% for PA/PE film, while the RH variation between 0 and 100% increased the OTR by 2.5-fold on average for this type of materials (De Leiris, 1989;Jakobsen et al, 2005). The exchanges through the film were then high enough to be measured.…”
Section: Cheese Respiratory Activitymentioning
confidence: 99%
“…The O2 concentration in the packaging is determined by the residual O2 after packaging, the respiration or consumption of O2 by the product, and by the O2 ingress during the shelf life (OTR) [34,35]. The simulation software PredOxyPack ® is a practical tool to predict the oxygen ingress for different packaging configurations, materials, and time-temperature profiles [36].…”
Section: Simulation Of the Oxygen Level In The Packagingmentioning
confidence: 99%
“…Small amounts of O 2 , when combined with exposure to light, cause significant oxidative deterioration of products (Jakobsen et al ., 2005). Many vacuum packagers or tray sealers do not remove air from packages with sufficient vacuum levels in the preferred amount of time for efficient packaging line speeds, so O 2 scavengers are used to create acceptably low-oxygen atmospheres in packages.…”
Section: Advances In Active Componentsmentioning
confidence: 98%